Electron microscopic detection of salivary α-amylase in the pellicle formed in situ - Deimling, Daniela; Breschi, Lorenzo; Hoth-Hannig, Wiebke; Ruggeri, Alessandra; Hannig, Christian; Nekrashevych, Yuriy; Prati, Carlo; Hannig, Matthias (European journal of oral sciences, 2004)
Immunological and biochemical analyses have shown that α‐amylase is an essential component of the acquired pellicle. After adsorption, this enzyme might act as a receptor for bacterial adherence. However, data indicating that amylase is bound to the pellicle surface in vivo and thus available for adhering bacteria are rare. Therefore, the present study focused on α‐amylase within the pellicle formed in situ, using gold‐immunolabeling electron microscopic techniques. Pellicles were formed by intra‐oral exposure of enamel specimens for 30 and 120 min in six subjects. The results obtained by transmission electron microscopy indicate that amylase was randomly distributed in the pellicle layer without any preferential localization within the pellicle. Thus, salivary α‐amylase might be considered as an important structural component that is even involved in the early stages of pellicle formation. The findings of field emission in‐lens scanning electron microscopy provided evidence that the enzyme is located on the pellicle surface. It could be concluded that α‐amylase might act as a receptor for bacterial adherence to the pellicle in vivo.